Pengaruh Modal Kerja dan Liabilitas Terhadap Earning Per Share Pada Perusahaan Semen yang Terdaftar di BEI Periode 2018-2022 - Maudy Diana Putri; Hurriyaturrohman, Hurriyaturrohman; Rumiasih, N.A. (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to investigate the influence of Working Capital and Liabilities on Earnings Per Share (EPS) both partially and simultaneously. It employs a quantitative research approach. The population consists of companies in the cement sub-sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022, totaling 6 companies. Purposive sampling was utilized to select the sample based on specific criteria, resulting in 3 companies with a market capitalization exceeding 10 trillion IDR being chosen. Data were sourced from the financial reports of each company published on the website www.idx.co.id. Data analysis was conducted using multiple regression analysis methods. The study was tested using SPSS software version 26. The results indicate that both Working Capital and Liabilities collectively influence Earnings Per Share in cement companies listed on the BEI from 2018 to 2022. Partially, Working Capital significantly affects Earnings Per Share, whereas Liabilities do not have a significant impact on Earnings Per Share.